Mucoadhesive role of tamarind xyloglucan on inflammation attenuates ulcerative colitis. (August 2018) - Periasamy, Srinivasan; Lin, Chia-Hui; Nagarajan, Balaji; Sankaranarayanan, Nehru Viji; Desai, Umesh R.; Liu, Ming-Yie
Graphical abstract: Highlights: Molecular docking studies revealed binding TXG to Mucin1 and cytokine receptors. TXG attenuated inflammation via mucoadhesion by decreasing cytokines. TXG attenuated inflammation via TLR4/NF-κB signaling pathway in UC model. Abstract: Tamarind xyloglucan (TXG) is edible, bioavailable and mucoadhesive polysaccharide. The aim of this study was (i) to investigate molecular docking studies on the interaction of TXG to MUC1 and cytokine receptors and (ii) to assess the mucoadhesive role of TXG in UC. In vivo study: C57Bl6 mice were administered with DSS 3% (w/v) in drinking water; TXG 100 or 300 mg/kg/day was given orally for 7 days simultaneously. TXG consistently binds to MUC1 and cytokine receptors in molecular docking studies. TXG decreased the expression of MUC1 and MUC2. The mucoadhesive ability of TXG decreased IL-1β and IL-6 levels. Furthermore, TXG decreased the expression of TLR4, MyD88, I-κB and NF-κB thereby attenuating inflammation via TLR4/NF-κB signaling pathway. TXG mucoadhesion to MUC1 played a pivotal role in attenuating inflammation. To conclude, the mucoadhesive role of TXG is important in the attenuation of inflammation and healing of UC.